Mathematics anxiety in primary education: A systematic review of foundations, causes, and interventions - Annisa, Annisa Qadri Tanjung; Arifin, Slamet; Faizah, Siti (Universitas Maritim Raja Ali Haji, 2024)
Mathematics anxiety (MA) is a common issue in primary education, negatively impacting students' academic performance, motivation, and confidence in mathematics. This study addresses existing gaps by systematically analyzing global trends, theoretical foundations, causes, and effective interventions for MA. A systematic literature review (SLR) was conducted using PRISMA guidelines, which included the stages of identification, screening, eligibility, and inclusion. Articles analyzed from the Scopus database were published between 2014 and 2024. The findings reveal a significant rise in MA research in recent years, with major contributions from China and the UK. Key theoretical foundations include anxiety and cognitive load theories, emphasizing the interplay between emotional and cognitive factors in MA development. Major causes of MA include cognitive limitations, gender, and curriculum. Effective interventions involve pedagogical approaches, psychological strategies, teacher support, and technology integration. These approaches include active learning, mindfulness techniques, and the use of interactive digital tools. This study highlights the importance of collaboration among educators, policymakers, and researchers to mitigate MA's impact and foster positive mathematical experiences for primary school students.